Fatmawati Nursing Academy Student Response to Online Learning During Pandemic Covid-19 - Agustina, Ayuda Nia (Universitas Aisyah Pringsewu, 2021)
The COVID-19 pandemic is a global pandemic, and this pandemic affects all aspects of human life, such as health, economy, food and clothing. The spread of this pandemic has resulted in the closure of public areas in the education sector, one of which is the Fatmawati Nursing Academy. The purpose of this study was to identify student responses to online learning during the Covid-19 period. This research design is quantitative with a survey method. The sampling technique in this study was cluster random sampling totalling 105 people who received online learning. The research was conducted from March to July 2020 at the Fatmawati Nursing Academy. The survey is made in the form of a questionnaire using google form which can be easily accessed by respondents. The data analysis technique uses a percentage of the score for each statement item. The results showed that: 1) the average respondent had a high or good response (70, 86%) to online learning during the pandemic; 2) The obstacles faced by students during online learning are internet networks, finance. Online learning during the pandemic at the Fatmawati Nursing Academy is considered effective but requires improvement in order to achieve the learning outcomes that have been formulated. Tanggapan Mahasiswa Akademi Keperawatan Fatmawati Terhadap Pembelajaran Online Selama Pandemi Covid-19Abstrak: Pandemi COVID-19 merupakan pandemi global, dan pandemic ini mempengaruhi seluruh aspek kehidupan manusia, seperti: Kesehatan, ekonomi, sandang pangan dan pendidikan. Adanya penyebaran pandemi ini menyebabkan penutupan-penutupan area umum di bidang pendidikan, salah satu yang terdampak adalah Akademi Keperawatan Fatmawati. Tujuan penelitian ini adalah mengidentifikasi tanggapan mahasiswa terhadap pembelajaran daring di masa Covid-19. Rancangan penelitian ini adalah kuantitatif dengan metode survey. Teknik pengambilan sampling pada penelitian ini adalah cluster random sampling berjumlah 105 orang yang mendapatkan pembelajaran daring. Penelitian dilaksanakan pada bulan Maret sampai dengan bulan Juli 2020 di Akademi Keperawatan Fatmawati. Survey dibuat dalam bentuk kuisioner menggunakan google form yang dapat mudah diakses oleh responden. Teknik Analisa data menggunakan presentase hasil skor untuk setiap butir pernyataan. Hasil penelitian menunjukkan bahwa: 1) rata-rata responden memiliki tanggapan yang tinggi atau baik (70, 86%) terhadap pembelajaran daring selama masa pandemi Covid-19; 2) Kendala yang dihadapi mahasiswa selama pembelajaran daring adalah jaringan internet dan keuangan. Pembelajaran daring selama masa pandemic Covid-19 di Akademi Keperawatan Fatmawati dinilai efektif, namun memerlukan perbaikan demi tercapai capaian pembelajaran yang telah dirumuskan.